Mobile Technology Acceptance Scale for Learning Mathematics: Development, Validity, and Reliability Studies - Açıkgül, Kübra; Şad, Süleyman Nihat (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
The purpose of this study is to develop a valid, reliable, and useful scale to measure high school students’ levels of acceptance of mobile technologies in learning mathematics based on the second version of the unified theory of acceptance and use of technology (UTAUT2) model. The study was designed based on a sequential exploratory mixed-method research design. To this end, both qualitative (interviews with students, review of literature, and expert panel evaluation) and quantitative procedures (Lawshe content validity technique, exploratory and confirmatory factor analysis, convergent validity, discriminant validity, nomological validity, criterion validity, internal consistency reliability, and temporal reliability) were used to develop and validate the Mobile Technology Acceptance Scale for Learning Mathematics (m-TASLM). As a result, a 5-point Likert scale with 36 items grouped under 8 factors was developed and confirmed. Both validity and reliability studies yielded favorable results.